On the Determination of the Public Debt - Barro, Robert J. (Journal of Political Economy, 1979)
A public debt theory is constructed in which the Ricardian invariance theorem is valid as a first-order proposition but where the dependence of excess burden on the timing of taxation implies an optimal time path of debt issue. A central proposition is that deficits are varied in order to maintain expect ed constancy in tax rates. This behavior implies a positive effect on debt issue of temporary increases in government spending (as in wartime) a countercyclical response of debt to temporary income movements, and a one-to-one effect of expected inflation on nominal debt growth. Debt issue would be invariant with the outstanding debt-income ratio and, except for a minor effect, with the level of government spending. Hypotheses are tested on U.S. data since World WXar1. Results are basically in accord Fith the theory. It also turns out that a small set of explanatory variables can account for the principal movements in interest-bearing federal debt since the 1920s.